Il metodo e l’uso degli strumenti religiosi di ADR negli ordinamenti statali - Lupano, Matteo (Comporre il conflitto, 2020)
This paper offers an overview of the importance of religious ADR – especially arbitration and mediation – in Western legal systems. In the US they have been used for over a hundred years, but since the XXI century they caused increasing hostility. Similar phenomena have occurred in Canada and the UK. The experience of common law countries highlights the potential of these instruments, but also the risks for vulnerable and marginalized individuals.